Estimation of rubber waste concrete properties by ultrasonic velocities: effect of transducers` diameters and frequencies - Boudjedra, Fatiha; Benouis, Abdelhalim; Boudaoud, Zineddine (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This experimental study aimed to use the ultrasonic pulse velocity method (UPV) in order to investigate the effect of rubber tire waste content and transducers` diameters and frequencies on the evolution of ultrasonic velocities in time and to elucidate the correlations between UPV and the properties of various concrete mixtures. The incorporation of this waste involved volume substitution (0, 5, 10, 15 and 20%) of fine aggregates (sand) by rubber waste (RW) granulates.
Keywords: rubber tire waste; rubberized concrete; compressive strength; porosity; ultrasonic pulse velocity; transducers; odpady opon; beton gumowany; wytrzymałość na ściskanie; porowatość